ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Wangarry, Reynold; Sondakh, Jullie; Budiarso, Novi S. (Universitas Sam Ratulangi, 2018)
PPAk is very important for students majoring in accounting, because PPAk can contribute to become a professional accountant. The purpose of this research is to analyze the factors that affect the interest of accounting student on accounting profession education (PPAk). Factors affecting the interest of accounting students are measured by variables of quality motivation, career motivation, economic motivation, and labor market considerations. This research applied survey as a method of primary data gathering from the population of accounting student of UNSRAT and STIE EBEN HAEZER MANADO, by using purposive sampling as the way to decide the sample. This research is using the multiple linear regression analysis using SPSS 22 version. The research indicates that: (1) quality motivation has a significant effect the interest of following accounting profession education, (2) career motivation has a significant effect the interest of accounting students following accounting profession education, (3) economic motivation has no significant effect the interest of accounting students following accounting profession education, (4) job market considerations has a significant effect the interest of accounting students following accounting profession education. Â Keywords: Quality Motivation, Career Motivation, Economic Motivaton, Job Market Considerations,Â Interest, Proffesion Accounting Education (PPAk).